Coherent driving of direct and indirect excitons in a quantum dot molecule - Bopp, Frederik; Schall, Johannes; Bart, Nikolai; Vögl, Florian; Cullip, Charlotte; Sbresny, Friedrich; Boos, Katarina; Thalacker, Christopher; Lienhart, Michelle; Rodt, Sven; Reuter, Dirk; Ludwig, Arne; et al. (Physical Review B)

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Modeling of Masked Droplet Deposition for Site-Controlled Ga Droplets - Feddersen, Stefan; Zolatanosha, Viktoryia; Alshaikh, Ahmed; Reuter, Dirk; Heyn, Christian (Nanomaterials)
Site-controlled Ga droplets on AlGaAs substrates are fabricated using area-selective deposition of Ga through apertures in a mask during molecular beam epitaxy (MBE). The Ga droplets can be crystallized into GaAs quantum dots using a crystallization step under As flux. In order to model the complex process, including the masked deposition of the droplets and a reduction of their number during a thermal annealing step, a multiscale kinetic Monte Carlo (mkMC) simulation of self-assembled Ga droplet formation on AlGaAs is expanded for area-selective deposition. The simulation has only two free model parameters: the activation energy for surface diffusion and the activation energy for thermal escape of adatoms from a droplet. Simulated droplet numbers within the opening of the aperture agree quantitatively with the experimental results down to the perfect site-control, with one droplet per aperture. However, the model parameters are different compared to those of the self-assembled droplet growth. We attribute this to the presence of the mask in close proximity to the surface, which modifies the local process temperature and the As background. This approach also explains the dependence of the model parameters on the size of the aperture.
Keywords: General Materials Science; General Chemical Engineering

Fachliche und überfachliche Herausforderungen in der Studieneingangsphase Physik - Bauer, Anna; Woitkowski, David; Reuter, Dirk; Reinhold, Peter (Hochschullehre erforschen.)
Die Studieneingangsphase Physik stellt für die Studienanfänger Innen einen komplexen Lernprozess mit vielfältigen Anforderungen auf fachlicher, Metakognitions- und Sozialisations-Ebene dar, der ihre akademische Identitätsbildung beeinflusst und prägt. Ziel des Projektes Paderborner Studieneingangsphase Physik (PSΦ) ist die evidenzbasierte Gestaltung eines strukturierten Studieneinstiegs und einer in sich kohärent abgestimmten Studieneingangsphase „aus einem Guss“. Die Implementation eines neuen Übungsformats (Präsenzübungen) in den Fachvorlesungen sowie die Unterstützung der Studierenden im Bereich des selbstregulierten Lernens zeigen positive Effekte in einer erhöhten Teilnahmequote sowie Zufriedenheit der Studierenden mit der Veranstaltung, in einem aktiveren Arbeitsverhalten sowie einer höheren Bestehensquote der Klausur. Ein messbar größerer Fachwissenserwerb konnte nicht nachgewiesen werden. Auf Basis der Evidenzen konnten Stellschrauben für die Weiterentwicklung sowie für die Unterstützung der Lehrenden abgeleitet werden. In dem Beitrag werden die Gelingensbedingungen und Strukturen für eine wirksame Zusammenarbeit von Fachdidaktik und Fachwissenschaft am Beispiel der Überarbeitung der Studieneingangsphase im Rahmen einer community of practice sowie der Wirksamkeit der Implementierung diskutiert.

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Scalable integration of quantum emitters into photonic integrated circuits - Sartison, M; Camacho Ibarra, O; Jöns, Klaus D.; Caltzidis, I; Reuter, Dirk

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Nonlinear down-conversion in a single quantum dot - Jonas, Björn; Heinze, Dirk Florian; Schöll, Eva; Kallert, Patricia; Langer, Timo; Krehs, Sebastian; Widhalm, Alex; Jöns, Klaus; Reuter, Dirk; Zrenner, Artur

Selective Etching of (111)B-Oriented AlxGa1−xAs-Layers for Epitaxial Lift-Off - Henksmeier, Tobias; Eppinger, Martin; Reineke, Bernhard; Zentgraf, Thomas; Meier, Cedrik; Reuter, Dirk (physica status solidi (a))
GaAs-(111)-nanostructures exhibiting second harmonic generation are new building blocks in nonlinear optics. Such structures can be fabricated through epitaxial lift-off using selective etching of Al-containing layers and subsequent transfer to glass substrates. Herein, the selective etching of (111)B-oriented AlxGa1−xAs sacrificial layers (10–50 nm thick) with different aluminum concentrations (x = 0.5–1.0) in 10% hydrofluoric acid is investigated and compared with standard (100)-oriented structures. The thinner the sacrificial layer and the lower the aluminum content, the lower the lateral etch rate. For both orientations, the lateral etch rates are in the same order of magnitude, but some quantitative differences exist. Furthermore, the epitaxial lift-off, the transfer, and the nanopatterning of thin (111)B-oriented GaAs membranes are demonstrated. Atomic force microscopy and high-resolution X-ray diffraction measurements reveal the high structural quality of the transferred GaAs-(111) films.
Keywords: epitaxial lift-off; GaAs/AlxGa1−xAs heterostructures; selective etching

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, D. J. (AIP Advances)

Suppression of nuclear spin fluctuations in an InGaAs quantum dot ensemble by GHz-pulsed optical excitation - Evers, E.; Kopteva, N. E.; Yugova, I. A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (npj Quantum Information)
Abstract The coherent electron spin dynamics of an ensemble of singly charged (In,Ga)As/GaAs quantum dots in a transverse magnetic field is driven by periodic optical excitation at 1 GHz repetition frequency. Despite the strong inhomogeneity of the electron g factor, the spectral spread of optical transitions, and the broad distribution of nuclear spin fluctuations, we are able to push the whole ensemble of excited spins into a single Larmor precession mode that is commensurate with the laser repetition frequency. Furthermore, we demonstrate that an optical detuning of the pump pulses from the probed optical transitions induces a directed dynamic nuclear polarization and leads to a discretization of the total magnetic field acting on the electron ensemble. Finally, we show that the highly periodic optical excitation can be used as universal tool for strongly reducing the nuclear spin fluctuations and preparation of a robust nuclear environment for subsequent manipulation of the electron spins, also at varying operation frequencies.

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (AIP Advances)

Two-dimensional lateral surface superlattices in GaAs heterostructures with independent control of carrier density and modulation potential - Wang, D. Q.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R.; Klochan, O. (Applied Physics Letters)

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K.N. (Journal of Crystal Growth)

Electrostatic potential shape of gate-defined quantum point contacts - Geier, M.; Freudenfeld, J.; Silva, J. T.; Umansky, V.; Reuter, Dirk; Wieck, A. D.; Brouwer, P. W.; Ludwig, S. (Physical Review B)

Characterization of low-resistance ohmic contacts to a two-dimensional electron gas in a GaAs/AlGaAs heterostructure - Javaid Iqbal, Muhammad; Reuter, Dirk; Wieck, Andreas Dirk; van der Wal, Caspar (The European Physical Journal Applied Physics)
The study of electron transport in low-dimensional systems is of importance, not only from a fundamental point of view, but also for future electronic and spintronic devices. In this context heterostructures containing a two-dimensional electron gas (2DEG) are a key technology. In particular GaAs/AlGaAs heterostructures, with a 2DEG at typically 100 nm below the surface, are widely studied. In order to explore electron transport in such systems, low-resistance ohmic contacts are required that connect the 2DEG to macroscopic measurement leads at the surface. Here we report on designing and measuring a dedicated device for unraveling the various resistance contributions in such contacts, which include pristine 2DEG series resistance, the 2DEG resistance under a contact, the contact resistance itself, and the influence of pressing a bonding wire onto a contact. We also report here a recipe for contacts with very low resistance values that remain below 10 Ω for annealing times between 20 and 350 s, hence providing the flexibility to use this method for materials with different 2DEG depths. The type of heating, temperature ramp rate and gas forming used for annealing is found to strongly influence the annealing process and hence the quality of the resulting contacts.

Electrical detection of excitonic states by time-resolved conductance measurements - Ebler, C.; Labud, P. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Ludwig, A. (Physical Review B)

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Excess noise in Al x Ga 1 − xAs/GaAs based quantum rings - Riha, Christian; Buchholz, Sven S.; Chiatti, Olivio; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (Applied Physics Letters)

Two-dimensional electron bound hole photoluminescence in GaAs in perpendicular magnetic fields - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Strain-driven InAs island growth on top of GaAs(111) nanopillars - Riedl, T.; Kunnathully, V. S.; Trapp, A.; Langer, T.; Reuter, Dirk; Lindner, J. K. N. (Physical Review Materials)

Strain-driven InAs island growth on top of GaAs(111) nanopillars - Riedl, Thomas; Kunnathully, V. S.; Trapp, A.; Langer, T.; Reuter, Dirk; Lindner, Jörg (Physical Review Materials)
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Electrically controlled rapid adiabatic passage in a single quantum dot - Mukherjee, Amlan; Widhalm, Alex; Siebert, Dustin; Krehs, Sebastian; Sharma, Nandlal; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
Keywords: tet_topic_qd

Ultrafast electric control of a single QD exciton - Förstner, Jens; Widhalm, A.; Mukherjee, A.; Krehs, S.; Jonas, B.; Spychala, K.; Förstner, Jens; Thiede, Andreas; Reuter, Dirk; Zrenner, Artur (11th International Conference on Quantum Dots)

Molecular beam epitaxy growth and temperature-dependent electrical characterization of carbon-doped GaAs on GaAs(1 1 1)B - Henksmeier, Tobias; Shvarkov, Stepan; Trapp, Alexander; Reuter, Dirk (Journal of Crystal Growth)

Germanium doping of cubic GaN grown by molecular beam epitaxy - Deppe, M.; Gerlach, J. W.; Shvarkov, S.; Rogalla, D.; Becker, H.-W.; Reuter, Dirk; As, Donat Josef (Journal of Applied Physics)

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Strain Relaxation in InAs Nanoislands on top of GaAs (111) A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

MBE Growth of InAs on Nanopillar-Patterned GaAs (111) A - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Basic Requirements of Spin-Flip Raman Scattering on Excitonic Resonances and Its Modulation through Additional High-Energy Illumination in Semiconductor Heterostructures - Debus, J.; Kudlacik, D.; Sapega, V. F.; Shamirzaev, T. S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Waag, A.; Bayer, M. (Physics of the Solid State)

Formation of self-assembled GaAs quantum dots via droplet epitaxy on misoriented GaAs(111)B substrates - Trapp, Alexander; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Site-controlled droplet epitaxy of GaAs quantum dots by deposition through shadow masks - Zolatanosha, Viktoryia; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Optical Properties of Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Theory of spin inertia in singly charged quantum dots - Smirnov, D. S.; Zhukov, E. A.; Kirstein, E.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A.; Glazov, M. M. (Physical Review B)

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

Correlation of the Carrier Decay Time and Barrier Thickness for Asymmetric Cubic GaN/Al0.64Ga0.36N Double Quantum Wells - Wecker, Tobias; Callsen, Gordon; Hoffmann, Axel; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Linear and nonlinear behaviour of near-IR intersubband transitions of cubic GaN/AlN multi quantum well structures - Wecker, T.; Jostmeier, T.; Rieger, T.; Neumann, E.; Pawlis, A.; Betz, M.; Reuter, Dirk; As, Donat Josef (Journal of Crystal Growth)

Incorporation of germanium for n-type doping of cubic GaN - Deppe, Michael; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Optical Properties of Germanium Doped Cubic GaN - As, Donat Josef; Deppe, Michael; Gerlach, Jürgen; Reuter, Dirk (MRS Advances)

Overcoming Ehrlich-Schwöbel barrier in (1 1 1)A GaAs molecular beam epitaxy - Ritzmann, Julian; Schott, Rüdiger; Gross, Katherine; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

Robust Si 3 N 4 masks for 100 nm selective area epitaxy of GaAs-based nanostructures - Zolatanosha, Viktoryia; Reuter, Dirk (Microelectronic Engineering)

Focused ion beam supported growth of monocrystalline wurtzite InAs nanowires grown by molecular beam epitaxy - Scholz, Sven; Schott, Rüdiger; Labud, Patrick A.; Somsen, Christoph; Reuter, Dirk; Ludwig, Arne; Wieck, Andreas D. (Journal of Crystal Growth)

Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Detection and Control of Spin-Orbit Interactions in a GaAs Hole Quantum Point Contact - Srinivasan, A.; Miserev, D. S.; Hudson, K. L.; Klochan, O.; Muraki, K.; Hirayama, Y.; Reuter, Dirk; Wieck, A. D.; Sushkov, O. P.; Hamilton, A. R. (Physical Review Letters)

InAs heteroepitaxy on GaAs patterned by nanosphere lithography - Kunnathully, Vinay; Riedl, Thomas; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Group III arsenide heteroepitaxy on Si(111) using SiNx nanohole masks patterned by nanosphere lithography - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Optical Transitions between Confined and Unconfined States in p-Type Asymmetric GaAs/InGaAs/AlGaAs QW Structures - Sitarek, P.; Ryczko, K.; Misiewicz, J.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

Exciton Exchange between Nearly-Free and Acceptor-Bound States of a Positive Trion Assisted by Cyclotron Excitation - Jadczak, J.; Bryja, L.; Wójs, A.; Bartsch, G.; Yakovlev, D.R.; Bayer, M.; Plochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

A modified gradient approach for the growth of low-density InAs quantum dot molecules by molecular beam epitaxy - Sharma, Nandlal; Reuter, Dirk (Journal of Crystal Growth)

Polaron-induced lattice distortion of (In,Ga)As/GaAs quantum dots by optically excited carriers - Tiemeyer, S; Bombeck, M; Göhring, H; Paulus, M; Sternemann, C; Nase, J; Wirkert, F J; Möller, J; Büning, T; Seeck, O H; Reuter, Dirk; Wieck, A D; et al. (Nanotechnology)

Thermal energy and charge currents in multi-terminal nanorings - Kramer, Tobias; Kreisbeck, Christoph; Riha, Christian; Chiatti, Olivio; Buchholz, Sven S.; Wieck, Andreas D.; Reuter, Dirk; Fischer, Saskia F. (AIP Advances)

Electric field distribution and exciton recombination line shape in GaAs - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Materials Research Express)

Photoluminescence excitation spectroscopy of excited states of an asymmetric cubic GaN/Al0.25Ga0.75N double quantum well grown by molecular beam epitaxy - Wecker, Tobias; Callsen, Gordon; Hoffmann, Axel; Reuter, Dirk; As, Donat Josef (Japanese Journal of Applied Physics)

Stabilizing nuclear spins around semiconductor electrons via the interplay of optical coherent population trapping and dynamic nuclear polarization - Onur, A. R.; de Jong, J. P.; O'Shea, D.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review B)

Heat flow, transport and fluctuations in etched semiconductor quantum wire structures - Riha, Christian; Chiatti, Olivio; Buchholz, Sven S.; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (physica status solidi (a))

Reconstruction of nuclear quadrupole interaction in (In,Ga)As/GaAs quantum dots observed by transmission electron microscopy - Sokolov, P. S.; Petrov, M. Yu.; Mehrtens, T.; Müller-Caspary, K.; Rosenauer, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Evidence of Singlet-Triplet Crossing in Photoluminescence of Positively Charged Excitons in GaAs Quantum Wells - Bryja, L.; Wójs, A.; Jadczak, J.; Misiewicz, J.; Płochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

From Localised to Ballistic Excitons in GaAs Quantum Wells - Pulizzi, F.; Christianen, P.C.M.; Maan, J.C.; Eshlaghi, S.; Reuter, Dirk; Wieck, A.D. (Acta Physica Polonica A)

From Localised to Ballistic Excitons in GaAs Quantum Wells - Pulizzi, F.; Christianen, P.C.M.; Maan, J.C.; Eshlaghi, S.; Reuter, Dirk; Wieck, A.D. (Acta Physica Polonica A)

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Nuclear spin polarization in the electron spin-flip Raman scattering of singly charged (In,Ga)As/GaAs quantum dots - Debus, J.; Kudlacik, D.; Sapega, V. F.; Dunker, D.; Bohn, P.; Paßmann, F.; Braukmann, D.; Rautert, J.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transform-limited single photons from a single quantum dot - Kuhlmann, Andreas V.; Prechtel, Jonathan H.; Houel, Julien; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Nature Communications)

Influence of Post-Implantation Annealing Parameters on the Focused Ion Beam Directed Nucleation of InAs Quantum Dots - Mehta, M.; Reuter, Dirk; Kamruddin, M.; Tyagi, A. K.; Wieck, A. D. (Nano)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Extending the spectral range of CdSe/ZnSe quantum wells by strain engineering - Finke, A.; Ruth, M.; Scholz, S.; Ludwig, A.; Wieck, A. D.; Reuter, Dirk; Pawlis, A. (Physical Review B)

Investigation of cubic GaN quantum dots grown by the Stranski-Krastanov process - Bürger, M.; Lindner, Jörg; Reuter, Dirk; As, D. J. (physica status solidi (c))
We investigate the formation of cubic GaN quantum dots (QDs) on pseudomorphic strained cubic AlN layers on 3C-SiC (001) substrates grown by means of molecular beam epitaxy. Surface morphologies of various QD sizes and densities were obtained from uncapped samples by atomic force microscopy. These results were correlated with similar but capped samples by photoluminescence experiments. The QD density varies by one order of magnitude from ~1x10^10 cm^-2 to ~1x10^11 cm^-2 as a function of the GaN coverage on the surface. The initial layer thickness for the creation of cubic GaN QDs on cubic AlN was obtained to 1.95 monolayers by a comparison between the experimental results and an analytical model. Our results reveal the strain-driven Stranski-Krastanov growth mode as the main formation process of the cubic GaN QDs.

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))
We analyse an InAs/GaAs-based electric ﬁeld tunable single quantum dot diode with a thin tunnelling barrier between a buried n þ -back contact and a quantum dot layer. In voltage- dependent photoluminescence measurements, we observe rich signatures from spatially direct and indirect transitions from the wetting layer and from a single quantum dot. By analysing the Stark effect, we show that the indirect transitions result from a recombination between conﬁned holes in the wetting or quantum dot layer with electrons from the edge of the Fermi sea in the back contact. Using a 17 nm tunnel barrier which provides comparably weak tunnel coupling allowed us to observe clear signatures of direct and corresponding indirect lines for a series of neutral and positively charged quantum dot states.
Keywords: excitons; GaAs; InAs; quantum dots; spatially indirect transitions; Stark shift

Photonic crystal cavities with metallic Schottky contacts - Quiring, W.; Al-Hmoud, M.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Applied Physics Letters)
We report about the fabrication and analysis of high Q photonic crystal cavities with metallic Schottky-contacts. The structures are based on GaAs n-i membranes with an InGaAs quantum well in the i-region and nanostructured low ohmic metal top-gates. They are designed for photocurrent readout within the cavity and fast electric manipulations. The cavity structures are characterized by photoluminescence and photocurrent spectroscopy under resonant excitation. We find strong cavity resonances in the photocurrent spectra and surprisingly high Q-factors up to 6500. Temperature dependent photocurrent measurements in the region between 4.5K and 310K show an exponential enhancement of the photocurrent signal and an external quantum efficiency up to 0.26.

Structural and optical properties of MBE-grown asymmetric cubic GaN/AlxGa1-xN double quantum wells - Wecker, T.; Hörich, F.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Magnetoconductance of a magnetic double barrier in a quantum wire - Schüler, B.; Cerchez, M.; Xu, Hengyi; Heinzel, T.; Reuter, Dirk; Wieck, A.D. (Superlattices and Microstructures)

Confocal shift interferometry of coherent emission from trapped dipolar excitons - Repp, J.; Schinner, G. J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Wurstbauer, U.; Kotthaus, J. P.; Holleitner, A. W. (Applied Physics Letters)

Observation of quantum states without a semiclassical equivalence bound by a magnetic field gradient - Schüler, B.; Cerchez, M.; Xu, Hengyi; Schluck, J.; Heinzel, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin-flip Raman scattering of the resident electron in singly charged (In,Ga)As/GaAs quantum dot ensembles - Debus, J.; Sapega, V. F.; Dunker, D.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

All-optical implementation of a dynamic decoupling protocol for hole spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Excitation of complex spin dynamics patterns in a quantum-dot electron spin ensemble - Varwig, S.; Yugova, I. A.; René, A.; Kazimierczuk, T.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Magnetic properties of Gd-doped GaN - Shvarkov, Stepan; Ludwig, Astrid; Wieck, Andreas Dirk; Cordier, Yvon; Ney, Andreas; Hardtdegen, Hilde; Haab, Anna; Trampert, Achim; Ranchal, Rocío; Herfort, Jens; Becker, Hans-Werner; Rogalla, Detlef; et al. (physica status solidi (b))

Time and spatially resolved electron spin detection in semiconductor heterostructures by magneto-optical Kerr microscopy - Henn, Tobias; Kießling, Tobias; Molenkamp, Laurens W.; Reuter, Dirk; Wieck, Andreas D.; Biermann, Klaus; Santos, Paulo V.; Ossau, Wolfgang (physica status solidi (b))